Corygaline A, a hexahydrobenzophenanthridine alkaloid with an unusual carbon skeleton from Corydalis bungeana Turcz. Issue 45 (9th November 2018) - Gao, Chang; Gu, Xiaoting; Wang, Xin; Cao, Huikun; Lin, Bin; Liu, Youping; Di, Xin
Abstract : A novel hexahydrobenzophenanthridine alkaloid, corygaline A (1 ), was isolated from Corydalis bungeana Turcz. Abstract : A novel hexahydrobenzophenanthridine alkaloid, corygaline A (1 ), was isolated from Corydalis bungeana Turcz. Its structure and absolute configuration were elucidated by spectroscopic data analysis and electronic circular dichroism (ECD) calculations. Corygaline A (1 ) is the first example of an alkaloid which features a 6/6/6/6/6-fused pentacyclic skeleton in nature. It exhibited significant NO production inhibitory activity in LPS-activated RAW264.7 macrophages with an IC50 value of 2.9 μM. A plausible biosynthetic pathway for1 is also discussed.